2023
DOI: 10.1111/dmcn.15712
|View full text |Cite
|
Sign up to set email alerts
|

Health care concerns in parents of children with different genetic developmental and epileptic encephalopathies: A qualitative study

Abstract: AimTo describe the experiences and unmet medical care needs of a group of parents of children with developmental and epileptic encephalopathies (DEEs) caused by the SCN1A, KCNQ2, CDKL5, PCDH19, and GNAO1 variants.MethodA qualitative descriptive study was conducted. Participants were recruited using purposeful sampling. The inclusion criteria consisted of parents of children with DEEs caused by the SCN1A, KCNQ2, CDKL5, PCDH19, or GNAO1 variants, aged between 4 and 10 years old. In total, 21 parents were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The present research is part of a larger qualitative study that described the experiences and unmet health care needs of parents of children with DEEs [27]. In this part of the study, our results show the impact that DEEs have on the parents and the couple's relationship as well as on the remaining family members.…”
Section: Discussionmentioning
confidence: 74%
“…The present research is part of a larger qualitative study that described the experiences and unmet health care needs of parents of children with DEEs [27]. In this part of the study, our results show the impact that DEEs have on the parents and the couple's relationship as well as on the remaining family members.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, in TSC, Zöllner et al (72) showed that there were discrepancies in the prioritization of the management of psychiatric and neurological symptoms between physicians and carers. Previous studies (12,54,74) in DEEs have shown the importance of the relationship with the healthcare professional for parents. For parents of children with SCN1A, KCNQ2, CDKL5, PCDH19, and GNAO1, the relationship was negative when professionals prioritized bureaucracy, ignored information provided by the family, communicated without empathy, judged the quality of home care, did not relate to their children, and did not understand the illness (12).…”
Section: Bdi-iimentioning
confidence: 98%
“…The interview question guide was developed based on previous studies concerning DEE (11,12,(53)(54)(55)(56) where a pilot test was conducted (52,57). All interviews were conducted by two researchers (MSPJ and DPC), with experience in developing qualitative studies using in-depth interviews and not involved in the care of the participants' children.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations